Relationship between body composition and vertical jump performance in young Spanish soccer players - Perez-Lopez, A.; Chena Sinovas, M.; Alvarez-Valverde, I.; Valades, D. (Journal of Sport and Human Performance, 2015)
The aim of this study was to examine the relative contribution of body composition to vertical jump performance in young Spanish soccer players. Seven hundred and twenty-three soccer players aged 7 to 19 years (156 ± 17 cm; 47.8 ± 15.1 kg) who had prior soccer experience (= 3 yrs) and had trained for ~2 h·day-1, 4 days·week-1 were selected. Anthropometric measurements were taken and three vertical jumps were performed: squat jump (SJ); counter-movement jump (CMJ); counter-movement jump with arm swing (CMJa). Multiple regression equations revealed that age (SJ, b = 0.635; CMJ, b = 0.687, CMJa, b = 0.674) and fat mass (SJ, b = -0.203; CMJ, b = -0.215, CMJa, b = -0.196) in children and age (SJ, b = 0.431; CMJ, b = 0.496; CMJa, b = 0.536), appendicular lean body mass (SJ, b = 0.214; CMJ, b = 0.160), and waist circumference (SJ, b = -0.187; CMJ, b = -0.119) in adolescents were the body composition variables that better explained vertical jump height. Thus, in addition to age, fat mass for children and appendicular lean body mass and waist circumference for adolescents may be used as body composition predictors to assess vertical jump performance in young soccer players.